The relationship of teacher’s immediacy to student motivation and student learning: a literature analysis - Zuria Mahmud; Mohammad Yaacob (penerbit ukm, 2007)
This article presented a literature review of research done on a construct that has been widely studied overseas but not yet done in Malaysia, that is, ‘teacher’s immediacy’. The focus of analysis is research on the relationship of teacher’s immediacy to student motivation and student learning. Conclusions drawn from the research shows that teacher’s immediacy is good for teachers, students and the teaching process. Method found to be most commonly used in measuring teacher’s immediacy is student report. Finally this paper discusse the implications of the findings on the field of research and education in Malaysia.